2011
DOI: 10.1016/j.meegid.2011.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Plasmodium vivax malaria in China and Myanmar

Abstract: Genetic diversity and population structure of Plasmodium vivax parasites are valuable to the prediction of the origin and spread of novel variants within and between populations, and to the program evaluation of malaria control measures. Using two polymorphic genetic markers, the merozoite surface protein genes PvMSP-3α and PvMSP-3β, we investigated the genetic diversity of four Southeast Asian P. vivax populations, representing both subtropical and temperate strains with dramatically divergent relapse pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 47 publications
4
33
2
Order By: Relevance
“…Seven patterns were detected in the pvmsp-3α gene after digestion of the PCR products with HhaI , with the most frequent allele variant being PH1 subtype. The results were consistent with those reported from other regions of the world, including those from Myanmar (n = 14) [7], Iran (n = 6) [14], Colombia (n = 9) [22], French Guiana (n = 11) [23], Thailand (n = 6) [28], Venezuela (n = 9) [29], and Peru (n = 17) [30]. However, outside Anhui province, the allele PH3, the second most common one in the present study, was the most prevalent in other areas of China including Hainan and Yunnan provinces, and also in Myanmar [7].…”
Section: Discussionsupporting
confidence: 92%
“…Seven patterns were detected in the pvmsp-3α gene after digestion of the PCR products with HhaI , with the most frequent allele variant being PH1 subtype. The results were consistent with those reported from other regions of the world, including those from Myanmar (n = 14) [7], Iran (n = 6) [14], Colombia (n = 9) [22], French Guiana (n = 11) [23], Thailand (n = 6) [28], Venezuela (n = 9) [29], and Peru (n = 17) [30]. However, outside Anhui province, the allele PH3, the second most common one in the present study, was the most prevalent in other areas of China including Hainan and Yunnan provinces, and also in Myanmar [7].…”
Section: Discussionsupporting
confidence: 92%
“…The reasons for the serious malaria epidemics in Yunnan Province may include its muggy tropical and subtropical climate, especially in tropical valleys [8, 9], and social factors such as the international movement of individuals to and from Laos, Myanmar and Vietnam. The trans-national population movement has been a major obstacle of effective malaria prevention and repetitive epidemics [10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…7,8 Previous studies have shown high genetic diversity but limited MOI among P. vivax infections in Southeast Asia. [9][10][11][12] However, the genotyping methods used in these studies are often limited in their ability to detect minority clones, leading to an underestimation of MOI. 8 The heteroduplex tracking assay (HTA) is a genotyping technique that has proven adept at uncovering minority variants within malaria infections and in infections with other agents.…”
Section: Introductionmentioning
confidence: 99%